Cloning and sequence analyses of cDNAs for interferon- and virus-induced human Mx proteins reveal that they contain putative guanine nucleotide-binding sites: functional study of the corresponding gene promoter. - Horisberger, M A (1990)
The human protein p78 is induced and accumulated in cells treated with type I interferon or with some viruses. It is the human homolog of the mouse Mx protein involved in resistance to influenza virus. A full-length cDNA clone encoding the human p78 protein was cloned and sequenced. It contained an open reading frame of 662 amino acids, corresponding to a polypeptide with a predicted molecular weight of 75,500, in good agreement with the Mr of 78,000 determined on sodium dodecyl sulfate gels for the purified natural p78 protein. The cloned gene was expressed in vitro and corresponded in size, pI, antigenic determinant(s), and NH2 terminus sequence to the natural p78 protein. A second cDNA was cloned which encoded a 633-amino-acid protein sharing 63% homology with human p78. This p78-related protein was translated in reticulocyte lysates where it shared an antigenic determinant(s) with p78. A putative 5' regulatory region of 83 base pairs contained within the gene promoter region upstream of the presumed p78 mRNA cap site conferred human alpha interferon (IFN-alpha) inducibility to the cat reporter gene. The p78 protein accumulated to high levels in cells treated with IFN-alpha. In contrast, the p78-related protein was not expressed at detectable levels. The rate of decay of p78 levels in diploid cells after a 24-h treatment with IFN-alpha was much slower than the rate of decay of the antiviral state against influenza A virus and vesicular stomatitis virus, suggesting that the p78 protein is probably not involved in an antiviral mechanism. Furthermore, we showed that these proteins, as well as the homologous mouse Mx protein, possess three consensus elements in proper spacing, characteristic of GTP-binding proteins.